GIS applications for site characterization and definition of recommendation domains - Lapar, Ma. Lucila (International Livestock Research Institute, 2000)
The first section of this paper presents a brief overview of the definition, structure, components, and functions of the Geographic Information Systems (GIS). Then the applications of GIS in crop-animal systems research is discussed with regard to benchmark site selection and characterisaiton; definition of recommendation domains; targeting of technology and policy interventions; and impact assessment of technology and policy interventions.